Effect of diets contains different rates of Fish Protein Concentrates on the Growth Rates of Carp Fingerlings Cyprinus carpio L. - Al-Hassoon, Ahmed Shihab (Iraqi Journal of Aquaculture, 2021)
The goal of this study is to investigate the effect of different ratios of fish protein concentrates (FPC), recovered by using salt solution (pure NaCl) 1% & 2% concentrate , on the growth and survival rates of carp fingerlings Cyprinus carpio L., three treatments had been made, A1& A2 contains the two made FPC and the third A3 contain commercial FPC, the three diets used in feeding 90 fish distributed on 9 plastic containers with capacity of 25 L., with three replicates for each treatment, 10 fingerlings were put in each replicate. The rates of relative growth, specific growth, food conversion were measured, it shows that A1 was the best treatment in the measurements, 76.87%, 1.854%, 2.375 respectively and A2 shows best survival rate 95%. Moreover the results shows significant differences (p< o.o5) between the treatments.